Evaluation of the antimicrobial effect and strength properties of polyester, polyester/cotton and cotton treated with Anolyte - Vermaas, Jana F. (University of the Free State, 2011)
Textile materials are usually treated with chemicals like sodium hypochlorite and high temperatures to ensure sterility. This poses two potential problems: (1) it has a negative effect on strength properties of the textile fabric; (2) the harmful chemicals are discarded into the environment. Therefore, better and safer methods need to be investigated. A process has been developed where electro-chemically activated water (Anolyte) is produced by an anode-cathode system and the process is described as a change of the molecular state of the water. After production, the Anolyte exists in a metastable state while containing many free radicals and a variety of molecules and a very high oxidation-reduction potential. It returns to a stable state after 48 hours and become inactive again and, therefore, it is not a threat to the environment when discarded after use. Anolyte has been shown to be an effective disinfection agent in other areas such as the food industry. The aim of this study was to determine if Anolyte could reduce E. coli and Staph. aureus on textiles to the same extent as sodium hypochlorite and be effective without implementing such high temperatures. The influence of the Anolyte on textile material should also be evaluated to ensure that it could be used without damaging textile materials more than the currently used disinfection agents. The antimicrobial effect of the Anolyte was determined by contaminating cotton, polyester and polyester/cotton fabric swatches with E. coli and Staph. aureus, respectively. Survival was determined after laundering with the respective wash liquors. AATCC Test Method 61- 2009 was used with the LaunderOmeter. Wash liquors included filtered water, phosphate reference detergent B, sodium hypochlorite and Anolyte. Temperatures were maintained at 24, 30 or 60°C. The cotton, polyester/cotton and polyester were laundered for 5, 10 or 20 cycles respectively for the evaluation of the influence on tensile strength and tearing strength. The tensile strength tests were conducted with the Instron Tensile Tester and ISO/SANS 13934-1:1999 test method. The tearing strength tests were conducted with the Elmendorf Tearing Strength tester as per ASTM Test Method D 1424 - 63. The results indicated that Anolyte destroyed all E. coli and Staph. aureus on all the fabrics regardless of the temperature. The effect of the other agents were enhanced by the increasing temperature, but after laundering at 60°C no survival was found as a result of the high temperature. The Anolyte did not influence the strength properties of the cotton, polyester and polyester/cotton fabrics to a larger extent than the detergent or sodium hypochlorite solution. An increase in maximum load required to break the fabric and displacement at maximum load was found for the cotton and polyester/cotton fabrics after laundering treatments, while a decrease was caused after laundering of the polyester fabric. A decrease in tearing strength of all the fabrics was found after laundering with the treatments. The Anolyte also did not affect the dimensional stability of the fabrics. It could be concluded that the Anolyte is a viable alternative to currently used sodium hypochlorite, while it is effective at low temperatures. The Anolyte do not affect the textile fabrics more negatively than the detergent and sodium hypochlorite combination, and could, therefore, be a successful alternative.

Tekstielstowwe word met chemikalieë soos natriumhipochloriet en hoë temperature behandel om dit te steriliseer. Dit hou twee potensiële probleme in: (1) dit het ‘n negatiewe effek op die sterkte eienskappe van die tekstielstof; en (2) die skadelike chemikalieë word in die natuur vrygestel. Dit lei tot die noodsaaklikheid om beter, veiliger onsmettingsmiddels te ondersoek. ‘n Proses is ontwikkel waar elektro-chemies geaktiveerde water (Anolyte) geproduseer word deur ‘n anode-katode sisteem en die proses word beskryf as die verandering van die molekulêre toestand van die water. Die “Anolyte” bestaan na produksie voort in ‘n metastabiele toestand en bevat baie vrye radikale en ‘n verskeidenheid molekules, asook ‘n baie hoë oksidasie-reduksie potensiaal. Dit keer terug na ‘n stabiele toestand na 48 uur en word dan weer onaktief, daarom is dit nie ‘n bedreiging vir die natuur nadat dit vrygestel is nie. Die doel van hierdie studie was om te bepaal of “Anolyte” die E. coli en Staph. aureus op tekstielstowwe tot dieselfde mate sal verminder as chemikalieë soos natriumhipochloriet, asook of dit effektief by lae temperature sal wees. Die invloed wat die “Anolyte” op tekstielstowwe het, moet ook ondersoek word om te verseker dat dit gebruik kan word sonder om meer skade aan te rig as die huidige ontsmettingsmiddels. Die antimikrobiese effek van die “Anolyte” is ondersoek deur katoen, poliëster en poliëster/katoen monsters onderskeidelik met E. coli en Staph. aureus te besmet. Oorlewing is bepaal nadat die tekstielmonsters gewas is met die onderskeie wasmiddels. AATCC Toetsmetode 61-2009 was gebruik met die “LaunderOmeter”. Die wasmiddels sluit in: gefiltreerde water, detergent, natriumhipochloriet en “Anolyte”. Temperature van 24, 30 of 60°C is gebruik. Die katoen, poliëster en poliëster/katoen tekstielstowwe is onderskeidelik vir 5, 10 of 20 siklusse gewas vir die evaluering van die invloed op treksterkte en skeursterkte. Die standaardmetodes is gebruik vir die bepaling van treksterkte (ISO/SANS 139341:1999) en skeursterkte (ASTM D 1424-63). Die resultate het aangedui dat “Anolyte” al die E. coli en Staph. aureus op al die tekstielstowwe vernietig het, ongeag die temperatuur. Die invloed van die ander wasmiddels is deur verhoogde temperatuur verbeter, maar nadat daar teen 60°C gewas is, was daar geen oorlewing nie as gevolg van die temperatuur en nie as gevolg van die wasmiddels nie. Die “Anolyte” het nie die sterkte-eienskappe van die katoen, poliëster en poliëster/katoen tot ‘n groter mate beïnvloed as die detergent of natriumhipochloriet nie. ‘n Toename in maksimum krag om breekpunt te bereik en verplasing by maksimum krag is gevind vir die katoen en poliëster/katoen tekstielstowwe, maar ‘n afname is waargeneem vir die poliëster tekstielstof na die wassiklusse met al die wasmiddels. Die “Anolyte het ook nie die dimensionele stabiliteit van die tekstielstowwe beïnvloed nie. Daar kan afgelei word dat die “Anolyte” ‘n lewensvatbare alternatief is vir natriumhipochloriet as ontsmettingsmiddel wat huidiglik gebruik word en dit is ook effektief teen lae temperature. Die “Anolyte” het nie die tekstielstowwe meer negatief beïnvloed as die detergent en natriumhipochloriet kombinasie nie en daarom kan dit as ‘n suksesvolle alternatief aangewend word.
Thesis (Ph.D. (Consumer Science))--University of the Free State, 2011
Keywords: Polyester fibres; Anolytes; Cotton; Staphylococcus aureus; Escherichia coli; Disinfect; Polyester; Anolyte; Tensile strength; Tearing strength